The Effect Honey Has on SOD and Caspase9 Levels with Exposure to Cigarette Smoke in Wistar Rats - Ela Fentri; Israhnanto Isradji; Setyo Trisnadi (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
Cigarettes are a source of exogenous free radicals which disrupt the balance between free radicals and antioxidants in the body, causing oxidative stress. The aim of this study was to determine the effect of giving honey (Mel depuratum) on SOD and caspase-9 levels in Wistar rats exposed to cigarette smoke. This research used a laboratory experimental approach with a post-test only control group design. 24 Wistar rats were divided randomly into 4 groups then analysis tests were carried out using the One-Way ANOVA test and followed by the Post-Hoc LSD test. The results showed that the mean SOD levels in groups K1, K2, K3, K4 were 73.51 ± 1.68, 21.72 ± 2.23, 52.08 ± 2.03, and 73.51 ± 1.68. The results of the One Way Anova test showed a significant difference in SOD levels with a value of p = 0.000. The results of the LSD Post-Hoc Test showed that SOD levels between groups had significant differences in all groups (p=0.000). The IHK staining results showed that samples K1 and K4 were negative, while K2 showed strong positive and K3 was moderately positive.